EFFECT OF PROTEIN LEVELS IN EARLY AGES IN SOME REPRODUCTIVE PARAMETERS IN JAPANESE QUAIL - Samah Maiser Raowf (Mesopotamia Journal of Agriculture)
This is study was carried out of the Poultry Field , Department of Animal Resource , College of Agriculture , Tikrit University, during the period 31-10-2011 to 6-2-2012, to evaluates of the effect of protein levels in early ages in reproductive performance in Japanese quail . A total number of 240 birds (180 female and 60 male), were used in this study female were randomly distributed to 4 treatments groups of 3 replicates each and each replicate constituted of (3 female : 1 male). Experimental treatments were T1 control diet (24% protein), T2 , T3 and T4 included addition 22, 20 and 18% protein respectively. The results showed that : the bird feeder on the diets of different protein levels during the early ages did not affect both the rate of fertility, hatchability of fertile eggs, hatchability of eggs total, embryonic mortality and weights of reproductive organs female and male . Results indicate that the rationing of food in the reconstruction of early (during the period of reining ) significant effect (p <0.05) in some of the eggs qualities , a significant second and fourth treatments to the transaction the third in the character of the relative weight of the crust at the time production total (6-17 weeks). While significantly outperformed (p <0.05) treatment in the character of the fourth the thickness of on first, second and third treatments when the first production period (6-9 weeks). While egg yolk weight and percentage of significant differences between the treatments.